Law, war, and warming: The new frontiers of climate security - Takaindisa, Joyce; Taiwo, Ibukun (2025)
As 2025 draws to a close, the climate-security agenda feels less like a niche debate, growing sharper, more complex, and perhaps for the first time, more actionable.